Creating a generic methodology for the determination of food dyes in food products; Химия и химическая технология в XXI веке; Т. 2 - Levchenko O. N. (Химия и химическая технология на иностранном языке Chemistry and Chemical Engineering, in English, 2013)
Заглавие с титульного экрана